The Impact of Qardhul Hasan Financing Using Zakah Funds on Economic Empowerment (Case Study of Dompet Dhuafa, West Java, Indonesia) - Febianto, Irawan; Ashany, Arimbi Mardilla (Asian Business Review, 2012)
Poverty has been one of the major economic issues that have been troubling in Indonesia for decades. This study intends to investigate whether the Qardhul Hasan Financing through Sinergi of Dompet Dhuafa in West Java, Indonesia, as zakah managing organization, is able to improve the recipients’ Economic Empowerment. The statistical results of the study show that the Qardhul Hasan Financing implemented by the organization is able to improve Economic Empowerment.
Keywords: Qardhul Hasan; Zakah funds; Economic; Empowerment; Microfinance